Modelo de atenção à criança com cardiopatia congênita em um hospital de referência da Paraíba - Souza, Bruno Leandro de (2017)
In Paraíba, until October 2011, there was no action directed at children with congenital heart disease. With the creation of the Pernambuco-Paraíba Pediatric Cardiology Network, the structuring of the pediatric cardiology service was started. Our objective in this study was to verify the impact of the implantation of the Pediatric Cardiology Network with the use of telemedicine in the care of children with congenital heart disease in the Arlinda Marques Pediatric Hospital from 2012. Method: This was a transversal in the Arlinda Marques Pediatric Hospital (CPAM), a reference hospital in the state of Paraíba for high complexity child care, located in the city of João Pessoa / PB. Clinical data (types of heart disease diagnosed and treated with surgical procedure, year of the procedure) and sociodemographic data (age group, sex, municipality of origin and characteristics of the municipality) were analyzed from records of children with congenital heart disease who performed CPAM surgery between 2010 and 2013. The data were analyzed by comparative tests between groups and tests of comparison of means that were defined after initial analysis of the data, considering that the value of ""p"" less than 0,05. Statistical analyzes were performed using software R. Results: Data from 260 patients were analyzed. There was an increase in the number of procedures after the implantation of the network from 99 to 163. 78% of the procedures were PCA, CIA, CIV and T4F, being statistically significant the increase after the implantation of the network for the procedures in patients with VSD (p = 0.03) and T4F (p = 0.04). The increase in procedures in the period 2012-2013 was statistically significant for children less than 1 years old (p = 0.01) and from the Sertão and Paraiba¿s Agreste (p <0.01). There was also a positive correlation between the period after the implementation of the program and assistance to children in municipalities with a lower percentage of urban area (p <0.001). Conclusion: The Network, which uses telemedicine as a fundamental tool to internalize and democratize health care, has had a positive impact on the care of children with congenital heart disease in the state of Paraíba, by increasing the number of services to children with congenital heart disease, especially In children under 1 year of age, and to expand the service coverage area, especially for the mesoregions of the hinterland and Agreste and municipalities with the highest percentage in the rural area.